Public speaking for engineering students in a blended learning environment - Ainol Haryati, Ibrahim; Nik Aloesnita, Nik Mohd Alwi (IEEE, 2018)
Effective teaching and learning processes are made possible as information and communication technology (ICTs) tools are used to support the environment. Today, apart from a fully face-to-face or online environment, blended learning promises opportunities for teaching and learning to be done in both environments. This study employed the quasi-experimental, pretest-posttest design to investigate the effects of blended learning in reducing anxiety and improving public speaking skills of ESL learners. Fifty-six students, enrolled in the fifth semester of the Bachelor in Civil Engineering program at a technical university in Malaysia, were involved in the study. The Personal Report of Public Speaking Anxiety (PRPSA) was administered as the pre and post test to measure the students' level of anxiety pertaining to public speaking. The Competent Speaker Speech Evaluation Form (CSSEF) was used as an instrument to measure the students' public speaking performance at pre and post conditions. The findings indicate that blended learning environment does have a positive impact in the development of public speaking skills of these students.